Media in the era of globalization in Latin America - Margarit, Rosa María (2003)
Globalization refers today to a change set whose intensity is unprecedented in the history of mankind. In an attempt to understand the mass media, the author have been quite rightly prosecutes in this phenomenon by resorting to the analysis and the confrontation of positions of different authors. It also gives an account of the incidence of the media in cultural identity, to finally refer its impact on education.